2015
DOI: 10.1093/sw/swv014
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Empathy in Burnout, Compassion Satisfaction, and Secondary Traumatic Stress among Social Workers

Abstract: Social workers are at risk for experiencing burnout and secondary traumatic stress (STS) as a result of the nature of their work and the contexts within which they work. Little attention has been paid to the factors within a social worker's control that may prevent burnout and STS and increase compassion satisfaction. Empathy, which is a combination of physiological and cognitive processes, may be a tool to help address burnout and STS. This article reports on the findings of a study of social workers (N = 173… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
211
2
22

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(253 citation statements)
references
References 30 publications
18
211
2
22
Order By: Relevance
“…[25] Some stressors have been identified for burnout of oncology nurses, including the nature of cancer, complex treatments, death, and intense involvement with patients and families,[26] however, findings showed those having a lower burnout score had higher empathy score, which is consistent with Brazeau et al .,[27] Paro et al .,[28] and Wagaman et al . [29] Concerning the components of burnout, the findings showed that the best predictor for nurses’ empathy were scores of lack of personal accomplishment, depersonalization, and emotional exhaustion, which is in line with Hojat et al . and Brazeau et al .…”
Section: Discussionsupporting
confidence: 79%
“…[25] Some stressors have been identified for burnout of oncology nurses, including the nature of cancer, complex treatments, death, and intense involvement with patients and families,[26] however, findings showed those having a lower burnout score had higher empathy score, which is consistent with Brazeau et al .,[27] Paro et al .,[28] and Wagaman et al . [29] Concerning the components of burnout, the findings showed that the best predictor for nurses’ empathy were scores of lack of personal accomplishment, depersonalization, and emotional exhaustion, which is in line with Hojat et al . and Brazeau et al .…”
Section: Discussionsupporting
confidence: 79%
“…To be published in the Journal of Forensic Practice (in press) While one study (Wagaman et al, 2015) noted empathy was a significant factor in aiding social workers to cope with the factors related to burnout and secondary traumatic stress, and that it contributes to the maintenance of the well-being and longevity of staff in their career, other studies found more empathetic therapists have a higher risk of developing vicarious trauma (Braley, 2010;Osofsky, 2011;Weaks, 1999). This therefore suggests that the level of empathic concern may be a factor, and that getting the balance correct is important.…”
Section: Factors Contributing To Vicarious Traumamentioning
confidence: 99%
“…Training that To be published in the Journal of Forensic Practice (in press) focuses on self-awareness, emotional regulation, and affective response, both before entering the field and during their working career to mitigate secondary traumatic stress (Wagaman et al, 2015) is considered an effective approach.…”
Section: Personal Factors That Mitigate or Decrease Vicarious Traumamentioning
confidence: 99%
“…Integration of more contemporary understanding about introspective empathy has called for broadened perspectives while maintaining an internal locus of control (Kohut, 1978;Wagaman, Geiger, Shockley, & Segal, 2015). The social worker must have the courage to go with the client in order for the client to fully process and fully receive that interchange (Sinclair & Monk, 2005).…”
Section: Empathy Respondingmentioning
confidence: 99%